EFISIENSI PENGGUNAAN PUPUK ANORGANIK AKIBAT PENGGUNAAN PUPUK ORGANIK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG (Zea mays L) DI TANAH ULTISOL - Oesman, Roswita (Jurnal Online Pertanian Tropik, 2017)
The research effects to obtain inorganic fertilizer use efficiency to the use of organic fertilizer on the growth and yield of maize (Zea mays L) in Ultisol. This research was conducted at the experimental field, the Laboratory for Research and Technology Faculty of Agriculture, University of North Sumatra, Medan from August to November 2016. The the design used in this study is a randomized block design factorial using two factors: organic fertilizers (O) with treatment as follows: O0 = Without organic fertilizers, O1 = 100% of doses of organic fertilizer, O2 = 75% of doses of organic fertilizer, O3 = 50% of doses of organic fertilizer, O4 = 25% of doses of organic fertilizer. inorganic fertilizer application (A) with treatment as follows: A0 = Without inorganic fertilizers, A1 = 100% of doses of inorganic fertilizer recommendations, A2 = 75% of doses of inorganic fertilizer recommendations, A3 = 50% of doses of inorganic fertilizer recommendations, A4 = 25% of doses of inorganic fertilizer recommendations. The variables measured were: plant height, shoot dry weight, root dry weight, dry seed weight. Results showed that 100% Organic fertilizer can increase growth and yield of corn were higher in soil ultisol. This is indicated by their real influence on the growth of plant height ages 8 and 12 WAP, the weight of dry seed, uptake of N and P, but no significant effect on shoot dry weight, root dry weight and uptake K. Inorganic fertilizer application of 100% can increase growth and yield of corn was higher in soil ultisol. This is indicated by their real influence on the growth of plant height age 8 WAP, root dry weight and the weight of dry seed, but did not significantly affect plant height age of 12 WAP, shoot dry weight, uptake of N, P and K. The interaction of the two combination treatments showed significantly effect on the weight of dry seed.